Case Report: Intestinal Obstruction as a Late Presentation of Perforation of the Transverse Colon Following Blunt Abdominal Trauma - Caballero, José (Indian J Surg, 2017)
Colonic perforation associated with blunt abdominal trauma is rare. Even more so is the formation of an inflammatory adhesion preventing leakage into the peritoneum. We present a case of the above in which the patient presented 1 month later with intestinal obstruction which required surgical intervention. A 38-year-old male, victim of a road traffic accident (RTA), presented with multiple fractures in his extremities which had to be operated on and was later discharged without complications. He was readmitted 1 month following the trauma with intestinal obstruction. During the operation, a stenosing colonic adhesion due to bowel perforation following blunt abdominal trauma was discovered. Resection of the transverse colon and a termino-terminal colo-colonic anastomosis was performed.